Usefulness of mandibular third molar coronectomy assessed through clinical evaluation over three years of follow-up. Issue 2 (February 2015) - Kohara, K.; Kurita, K.; Kuroiwa, Y.; Goto, S.; Umemura, E.
Abstract The aim of this study was to investigate the 3-year morbidity of coronectomy of the lower third molar and to monitor the behaviour and migration pattern of the retained roots postoperatively. A total of 92 patients (111 teeth) who had undergone a coronectomy between October 2005 and July 2009 were investigated. Patients were followed up at 3 months and 1, 2, and 3 years for clinical evaluation and dental computed tomography imaging of the coronectomy sites. In total, 10 cases (9%) required tooth root extraction within the 3 years after coronectomy. In seven of them, the distal pocket of the lower second molars remained connected to the roots within the first year. Of the cases in whom a pocket did not remain at an early stage, none showed peri-apical lesions on transmission images of the retained roots in the apical area, which usually result from necrosis of the pulp. Root migration increased in the first 2 years after coronectomy but stabilized between the second and third years. In addition, a significant difference was noted in root migration between patients of different ages and sex. Retained roots after coronectomy in the lower third molars led to no complications in terms of infection or the development of pathologies within the first 3 years postoperatively.